OSSEOINTEGRATION OF DENTAL IMPLANTS: A REVIEW - Forna Norina (Romanian Dental Association for Education, 2020)
The osseointegration processes are based on post-implantation healing processes that are modeled by the activation by complex mechanisms of macrophages that leads to the differentiation of new osteoblasts on the implant surface. Factors influencing osseointegration include patient-related factors (systemic status), surgical factors (operating field asepsis, bone preparation time, operative trauma), and implant design factors (shape and dimensional characteristics, chemistry and surface topography, material). The quality of the implant biomaterial and the bone healing capacity followed by the bio-functional remodeling of the peri-implant tissues are the two major factors that ensure the maintenance of osseointegration and the quality of osteo-reception of dental implants. Research groups and manufacturers of implants with bioactive surfaces are focused on the increase of osseointegration by lowering the bacterial adhesion, while promoting the recruitment, adhesion and proliferation of osteogenic elements (osteoblast cells) and fibroblasts.